Effectiveness of Quizizz on Students’ Learning Motivation and Engagement in a Filipino Class - Lailani Margallo; Cherrylyn Cacharro; Jhonmar D. Bergula; Sweet Rose A. Villaflor; Mary Love Agner; Chirramae Bughao; Jelyka Calumpag; Caryl Calvara; Krisha Kate Jamen; Ajie Viniece Loresca; Danica Maanad; Justine Mae Refuerzo; Lorena M. Ripalda; Cristobal A. Rabuya (East Asian Journal of Multidisciplinary Research, 2023)
The educational community has started to look into how well gamification works as a way to learn. This study aimed to determine how using Quizizz in a Filipino class would change how motivated and interested the students were. The study used a modified questionnaire and quasi-experimental research design. Descriptive analysis, mean, percentage and standard deviation were used to assess students' motivation and interest in Quizizz and traditional instruction. A paired samples t-test was used to see if there was a difference between how motivated and engaged students were in learning in a Filipino class that used standard methods and one that used Quizizz. Based on the study, there was a big difference between the traditional way and Quizizz in how motivated and interested the students were in learning. The study found that using Quizizz in a Filipino class makes students more curious and want to learn more.